Distinct Expression Patterns of Interleukin-22 Receptor 1 on Blood Hematopoietic Cells in SARS-CoV-2 Infection - Albayrak, Nurhan; Orte Cano, Carmen; Karimi, Sina; Dogahe, David; Van Praet, Anne; Godefroid, Audrey; Del Marmol, Véronique; Grimaldi, David; Bondue, Benjamin; Van Vooren, Jean-Paul; Mascart, Françoise; Corbière, Véronique (Frontiers in Immunology, 2022)
The new pandemic virus SARS-CoV-2 is characterized by uncontrolled hyper-inflammation in severe cases. As the IL-22 / IL-22R1 axis was reported to be involved in inflammation during viral infections, we characterized the expression of IL-22 receptor1, IL-22 and IL-22 binding protein in COVID-19 patients. Blood samples were collected from 19 non-severe and 14 severe patients on the day they presented (D0), at D14, and six months later, and from 6 non-infected controls. The IL-22R1 expression was characterized by flow cytometry. Results were related to HLA-DR expression of myeloid cells, to plasma concentrations of different cytokines and chemokines and NK cells and T lymphocytes functions characterized by their IFN-, IL-22, IL-17A, granzyme B and perforin content. The numbers of IL-22R1+ classical, intermediate, and non-classical monocytes and the proportions of IL-22R1+ plasmacytoid DC (pDC), myeloid DC1 and DC2 (mDC1, mDC2) were higher in patients than controls at D0. The proportions of IL-22R1+ classical and intermediate monocytes, and pDC and mDC2 remained high for six months. High proportions of IL-22R1+ non-classical monocytes and mDC2 displayed HLA-DRhigh expression and were thus activated. Multivariate analysis for all IL-22R1+ myeloid cells discriminated the severity of the disease (AUC=0.9023). However, correlation analysis between IL-22R1+ cell subsets and plasma chemokine concentrations suggested pro-inflammatory effects of some subsets and protective effects of others. The numbers of IL-22R1+ classical monocytes and pDC were positively correlated with pro-inflammatory chemokines MCP-1 and IP-10 in severe infections, whereas IL-22R1+ intermediate monocytes were negatively correlated with IL-6, IFN-α and CRP in non-severe infections. Moreover, in the absence of in vitro stimulation, NK and CD4+ T cells produced IFN-γ and IL-22, and CD4+ and CD8+ T cells produced IL-17A. CD4+ T lymphocytes also expressed IL-22R1, the density of its expression defining two different functional subsets. In conclusion, we provide the first evidence that SARS-CoV-2 infection is characterized by an abnormal expression of IL22R1 on blood myeloid cells and CD4+ T lymphocytes. Our results suggest that the involvement of the IL-22R1/ IL-22 axis could be protective at the beginning of SARS-CoV-2 infection but could shift to a detrimental response over time.